PSYCHOLOGICAL DISORDERS IN BURN PATIENTS: A META-ANALYSIS OF DISORDERS AND TREATMENTS - Rima Kedadra,; Nfidsa Fatima, (International Journal of Innovative Technologies in Social Science, 2024)
The main subject of this paper is the psychological disorders experienced by burn patients, with a particular emphasis on the necessity of psychological intervention in their treatment. The research seeks to investigate prevalent mental health conditions, including post-traumatic stress disorder, depression, and anxiety, and assess the efficacy of various therapeutic approaches.The method relied on a comprehensive review of prior literature and a thorough evaluation of the outcomes from relevant studies. The findings indicated that a significant portion of burn victims experience various psychological disorders. This includes post-traumatic stress disorder (PTSD), depression impacting, and anxiety affecting. The research also highlighted the significance of providing psychosocial support to enhance treatment results, as well as the effectiveness of Eye Movement Desensitization and Reprocessing (EMDR), Cognitive-Behavioral Therapy (CBT) and Virtual Reality (VR) techniques in addressing these conditions.To ensure comprehensive and effective patient care, it is recommended to integrate psychological interventions into burn treatment protocols, as stated in the paper's conclusion.